2022
DOI: 10.1007/s11845-022-03207-3
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate proton pump inhibitor lansoprazole prescription in older adults hospitalized in long-term care unit

Abstract: Purpose We evaluated the use of the PPI treatment by physicians in older adults hospitalized in a long-term care unit. Methods We included 40 patients aged 65 years or older with a lansoprazole prescription hospitalized in long-term care unit from January 2018 to January 2022. Patient characteristics, gastroduodenal history, dose of lansoprazole, indication, days of prescription, and number of medications were collected from electronic patient records. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A 2008 study based at an outpatient geriatric practice found that 28% of those aged 65 and older had a current prescription for a PPI 10 . Another study performed in 2022 of older adults hospitalized in a long‐term care unit found that >50% of them were currently receiving a daily PPI 11 …”
Section: Discussionmentioning
confidence: 99%
“…A 2008 study based at an outpatient geriatric practice found that 28% of those aged 65 and older had a current prescription for a PPI 10 . Another study performed in 2022 of older adults hospitalized in a long‐term care unit found that >50% of them were currently receiving a daily PPI 11 …”
Section: Discussionmentioning
confidence: 99%